2002
DOI: 10.1053/eupc.2001.0207
|View full text |Cite
|
Sign up to set email alerts
|

What is the optimal electrode configuration for atrial defibrillators in man?

Abstract: The right atrium to coronary sinus electrode configuration significantly reduces the atrial DFT. The atrial DFT also remains stable at 3 months post-implantation. Patients with persistent AF undergoing insertion of an atrial defibrillator should have a coronary sinus electrode implanted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Placement of shocking electrodes in the coronary sinus has been more commonly seen in atrial defibrillators. Shock vectors incorporating the coronary sinus have been shown to reduce atrial DFTs in patients with AF 9,10 …”
Section: Discussionmentioning
confidence: 99%
“…Placement of shocking electrodes in the coronary sinus has been more commonly seen in atrial defibrillators. Shock vectors incorporating the coronary sinus have been shown to reduce atrial DFTs in patients with AF 9,10 …”
Section: Discussionmentioning
confidence: 99%
“…Once the audible tones are heard, there is a period of anxiety in preparation for the shock, and it is likely that this increases the shock discomfort. Improved capacitor technology may reduce this delay, and methods to reduce the atrial defibrillation threshold below the pain threshold will improve the tolerability of the shock 6 …”
Section: Discussionmentioning
confidence: 99%
“…We thank Mitchell et al for their interest in our article 1 . The electrode configurations tested in their study 2 were different from ours 1 . Mitchell et al showed that atrial defibrillation threshold (ADFT) was lower in the right atrium (RA) coronary sinus (CS) vector than Can right ventricle (RV)+RA.…”
mentioning
confidence: 85%